Human XIST yeast artificial chromosome transgenes show partial X inactivation center function in mouse embryonic stem cells - Heard, Edith (The National Academy of Sciences, 1999)
Initiation of X chromosome inactivation requires the presence, in cis, of the X inactivation center (XIC). The Xist gene, which lies within the XIC region in both human and mouse and has the unique property of being expressed only from the inactive X chromosome in female somatic cells, is known to be essential for X inactivation based on targeted deletions in the mouse. Although our understanding of the developmental regulation and function of the mouse Xist gene has progressed rapidly, less is known about its human homolog. To address this and to assess the cross-species conservation of X inactivation, a 480-kb yeast artificial chromosome containing the human XIST gene was introduced into mouse embryonic stem (ES) cells. The human XIST transcript was expressed and could coat the mouse autosome from which it was transcribed, indicating that the factors required for cis association are conserved in mouse ES cells. Cis inactivation as a result of human XIST expression was found in only a proportion of differentiated cells, suggesting that the events downstream of XIST RNA coating that culminate in stable inactivation may require species-specific factors. Human XIST RNA appears to coat mouse autosomes in ES cells before in vitro differentiation, in contrast to the behavior of the mouse Xist gene in undifferentiated ES cells, where an unstable transcript and no chromosome coating are found. This may not only reflect important species differences in Xist regulation but also provides evidence that factors implicated in Xist RNA chromosome coating may already be present in undifferentiated ES cells.